A modified Steinberg–Cochran–Guinan model applicable to solid–liquid mixed zone along the principle Hugoniot. (April 2021) - Yang, Xin; Zeng, Xiangguo; Wang, Fang; Zhao, Han; Chen, Jun; Wang, Yuntian
Abstract: A constitutive model is vital for describing the deviatoric stresses of metallic materials under intense impact loading. Although the classical Steinberg–Cochran–Guinan (SCG) model has been widely regarded as an acceptable scheme, it does not clearly describe the coupling effect of the strain hardening and temperature softening at high temperatures and pressures, especially for the solid–liquid mixed phase. In this work, a modified SCG (MSCG) model is proposed based on an idealized assumption that the shear modulus and yield strength are equal to zero at the complete melting temperature and pressure. The temperature-dependent shear modulus model is then introduced in the MSCG model. The proposed model avoids the over-temperature softening effect by discarding the linear temperature term. More importantly, the pressure–temperature coupling factor ( k ) is employed in the pressure term, and the k adjusts the coupling effect of the strain hardening and temperature softening. In addition, the asymmetric relation in the MSCG model indicates that the temperature softening effect is more dominant than the strain hardening effect during the whole shock loading process. Moreover, the MSCG model is compared with the SCG model, Li and Chen's SCG model, and available data; the comparison verified the ability of the model to reproduce the shear moduli and yield strengths of Al, Be, Cu, and W in the solid–liquid mixed phase. Highlights: The temperature-dependent shear modulus model is introduced in the MSCG model. k can adjust the coupling effect of strain hardening and temperature softening. Temperature softening effect is more powerful than strain hardening effect. The validity of MSCG model in a solid-liquid mixed phase is examined well.